Magnetic properties of Sm-Co/Fe exchange spring magnets - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
The magnetic properties of Cr/Sm-Co/Fe/Cr multilayers epitaxially grown on MgO(1 1 0) substrate system have been studied by electron spin resonance (ESR) technique. ESR measurements have been carried out for various direction of DC magnetic field with respect to the crystalline axes. Both overall magnetization and ESR spectra exhibit very strong angular dependence. Analysis of the results shows that the easy axis of hard Sm - Co layer is not perfectly parallel to the film plane; rather it is slightly tilted (15 degrees) toward film normal. The deduced value for exchange coupling parameter between hard Sm - Co and soft Fe layers is about 80 kA/m. (C) 2004 Elsevier B. V. All rights reserved.
Keywords: ferromagnetic resonance; magnetic anisotropy; magnetic multilayer; magnetic recording material